2010
DOI: 10.4081/ijas.2010.e70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets with increasing levels of golden flaxseed on carcass characteristics, meat quality and lipid traits of growing rabbits

Abstract: The aim of this study was to determine the effects of three levels (0, 8, or 16%) of the golden variety of flaxseed (GFS; Linum usitatissimum L.), included in isonitrogenous and isocaloric diets, on the carcass characteristics, meat composition and fatty acid profile of rabbit meat and perirenal fat. The trial was carried out on 30 weaned crossbred rabbits aged 9 weeks, weighing on average 2074 g. The animals were divided equally into three groups of 10 (five male and five female rabbits each) and kept separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…In fact, Dalle Zotte (2002) reported an n-6/n-3 ratio of 11.6 for the rabbit hind leg, and Liu et al (2009) reported even higher values (around 14.6) for this ratio. Peiretti et al (2011b) found an n-6/n-3 ratio of 13.1 for the LD muscle of rabbits fed maize oil supplement diet, although values ranging from 1.1 to 1.9 for this ratio were found in the LD muscle of rabbits fed golden flaxseedsupplemented diets (Peiretti and Meineri, 2010). Moreover, in a trial using tomato by-products, Peiretti et al (2013) found similar values to those of the present study.…”
Section: Tbars Assaysupporting
confidence: 83%
“…In fact, Dalle Zotte (2002) reported an n-6/n-3 ratio of 11.6 for the rabbit hind leg, and Liu et al (2009) reported even higher values (around 14.6) for this ratio. Peiretti et al (2011b) found an n-6/n-3 ratio of 13.1 for the LD muscle of rabbits fed maize oil supplement diet, although values ranging from 1.1 to 1.9 for this ratio were found in the LD muscle of rabbits fed golden flaxseedsupplemented diets (Peiretti and Meineri, 2010). Moreover, in a trial using tomato by-products, Peiretti et al (2013) found similar values to those of the present study.…”
Section: Tbars Assaysupporting
confidence: 83%
“…The study has shown a very high variability of FAs in the diets that resulted from the variation coefficient (VC), which was only limited to less than 50% in 4 FAs but it exceeded 150% in 12 cases out of 20. The FA profiles of the diets, which differed according to the ingredients, are not analytically reported in the present study; as expected, the diets supplemented with oilseed (false flax [13], chia [14], linseed [15], and perilla [17]) had increased proportions of linoleic (C18:2 n-6) and α-linolenic acid (C18:3 n-3) with increasing supplementation level of seeds, while the unsupplemented diets or those supplemented with spirulina [12,16], curcuma [18], or tomato pomace [19] contained large amounts of palmitic (C16:0), oleic (C18:1 n-9) and linoleic acid.…”
Section: Resultssupporting
confidence: 58%
“…The FA profile of the diets, as well as the perirenal fat and longissimus dorsi muscle of the rabbits have been reported in eight papers [12,13,14,15,16,17,18,19]. Lipid extraction was performed on the diets, meat, and fat samples according to Hara and Radin [21], while the transesterification of the FAs was carried out according to Christie [22], with the modifications described by Chouinard et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Egg industry over the last decade has been penalised by a negative trend in per capita egg consumption possibly linked to the fact that eggs are a major dietary sources of cholesterol and consumers are concerned about the correlation between cholesterol intake and cardiovascular disease (Zazpe et al, 2011). In order to improve the nutritional profile of animal products omega-3 feed enrichment has been extensively investigated in many sectors such as poultry science (Cherian and Sim, 1991;Gonzalez-Esquerra and Leeson, 2001;Fraye et al, 2012), rabbit nutrition (Bernardini et al, 1999;Dal Bosco et al, 2004;Kouba et al, 2008;Peiretti and Meineri, 2010;Dal Bosco et al, 2014) as well as pig nutrition (Morgan et al, 1992;Leskanich et al, 1997). In recent years special attention has also been paid by dairy industries to improve the nutraceutical profile of milk by increasing the content of polyunsaturated fatty acids (PUFA) omega-3 FA (Dewhurst et al, 2006).…”
Section: Introductionmentioning
confidence: 99%